2012
DOI: 10.2319/072512-606.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride on root resorption following heavy and light orthodontic force application for 4 weeks and 12 weeks of retention

Abstract: Objective: To evaluate the null hypothesis that fluoride intake via drinking water has no effect on orthodontic root resorption in humans after orthodontic force application for 4 weeks and 12 weeks of retention. Materials and Methods: Forty-eight patients who required maxillary premolar extractions as part of their orthodontic treatment were selected from two cities in Turkey. These cities had a high and low fluoride concentration in public water of $2 pm and #0.05 pm, respectively. The patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(37 reference statements)
1
4
0
2
Order By: Relevance
“…The results of the present study, namely a higher and significant fluoride concentration in nail clippings and hair collected from IC participants when compared to SC participants, are similar to the findings of other studies [1114]. These findings may be attributed to the fact that the regular level of fluoride in IC (≥2 ppm) drinking water was higher than that in SC (≤0.05 ppm) [18, 19]. Therefore, systemic fluoride circulation in the residents of IC is considerably higher, which in turn raised the fluoride uptake by nails and hair.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study, namely a higher and significant fluoride concentration in nail clippings and hair collected from IC participants when compared to SC participants, are similar to the findings of other studies [1114]. These findings may be attributed to the fact that the regular level of fluoride in IC (≥2 ppm) drinking water was higher than that in SC (≤0.05 ppm) [18, 19]. Therefore, systemic fluoride circulation in the residents of IC is considerably higher, which in turn raised the fluoride uptake by nails and hair.…”
Section: Discussionsupporting
confidence: 90%
“…No changes in the address of residency (< 3 months) particularly before the commencement of this study and no history of systemic or topical fluoride supplements existed. Twenty-four participants (12 males and 12 females, mean age 15.42 + 2.50 years) were from Isparta city (IC), in the southwestern part of Turkey, with a high fluoride concentration in the public water supply (≥2 ppm (ppm)) [18, 19]. The participants from IC had Thylstrup and Fejerskov Fluorosis Indices (TFI) ranging from 2 to 5 [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One rat study also reported a decrease in the surface roughness of resorption craters and a reduction in the amount of tooth movement [ 14 ]. There are only two human studies that compared OIIRR in individuals from high and low water fluoridation areas after 28 days of light or heavy (25 g or 225 g) buccal orthodontic force [ 15 , 16 ]. These studies reported significantly reduced volume of OIIRR with higher fluoride concentration (≥ 2 ppm) but only in the high force (225 g) group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em Ortodontia, a Micro-CT tem sido empregada nos trabalhos em animais que pesquisam remodelação óssea (FRANZEN et al, 2014;KRAUS et al, 2014) e reabsorção radicular (KARADENIZ et al, 2013;PONDER et al, 2013) decorrentes da movimentação ortodôntica, estabilidade de mini-implante e resposta óssea ao seu redor (MASSEY et al, 2012;DRESCHER, 2011;WU et al, 2014), características estruturais tridimensionais de bráquetes (KANG et al, 2013), mensuração da espessura das corticais ósseas e disponibilidade de espaço para inserção de mini-implantes em peças anatômicas(LAURSEN; MELSEN; CATTANEO, 2013;WILMES et al, 2006), entre outras aplicações. A avaliação do contato/perfuração radicular por mini-implantes geralmente tem sido feita através de análise histológica (AHMED et al, 2012;ASSCHERICKX et al, 2005;BRISCENO et al, 2009;SHIN;KYUNG, 2008;DAO et al, 2009;KIM, 2011;LEE et al, 2010;MAINO et al, 2007;RENJEN et al, 2009) TASDEMIR, 2011;HWANG, 2011;KURODA et al, 2007;MCCABE;KAVANAGH, 2012), muitas vezes limitadas por ser tratar de imagens bidimensionais (ASSCHERICKX et al, 2008), e por tomografia computadorizada de feixe cônico (KURODA et al, 2007;SHIGEEDA, 2014;SHINOHARA et al, 2013;SON et al, 2014;WATANABE et al, 2013) (BARROS et al, 2011;FLORVAAG et al, 2010;HWANG, 2008;WILMES et al, 2008a;<...>…”
Section: Microtomografia Computadorizadaunclassified